The Gehry House. A metaphorical use of materials as a speculative method to project - Rodríguez Fernández, Ángela (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
Frank Gehry considered the extension of his house as an experimental work which allowed him to reflect on the materialization of his architectural thinking. Among the goals he pursues in his projects stands out the reflection on the idea of beauty in architecture and its achievement by linking it to the reality of the project. One of the procedures applied in the extension of his house relate to the creative and speculative structure that characterize the metaphor as a way to transgress the conventions on beauty. By following such structure he used cheap and common materials differently from what is conventionally recognized, being this one of the features that differentiates the house. By using materials in a non-conventional manner he wanted to explore the aesthetical possibilities of those common materials which aesthetical qualities were normally ignored. The metaphorical application of those materials was a creative strategy used to redefine the project’s expression of beauty.